Optimization of transversal phacoemulsification settings in peristaltic mode using a new transversal ultrasound machine. Issue 9 (September 2017) - Wright, Dannen D.; Wright, Alex J.; Boulter, Tyler D.; Bernhisel, Ashlie A.; Stagg, Brian C.; Zaugg, Brian; Pettey, Jeff H.; Ha, Larry; Ta, Brian T.; Olson, Randall J.
Abstract : Purpose : To determine the optimum bottle height, vacuum, aspiration rate, and power settings in the peristaltic mode of the Whitestar Signature Pro machine with Ellips FX tip action (transversal). Setting : John A. Moran Eye Center Laboratories, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Porcine lens nuclei were hardened with formalin and cut into 2.0 mm cubes. Lens cubes were emulsified using transversal and fragment removal time (efficiency), and fragment bounces off the tip (chatter) were measured to determine optimum aspiration rate, bottle height, vacuum, and power settings in the peristaltic mode. Results : Efficiency increased in a linear fashion with increasing bottle height and vacuum. The most efficient aspiration rate was 50 mL/min, with 60 mL/min statistically similar. Increasing power increased efficiency up to 90% with increased chatter at 100%. Conclusion : The most efficient values for the settings tested were bottle height at 100 cm, vacuum at 600 mm Hg, aspiration rate of 50 or 60 mL/min, and power at 90%.